Synergy Between the Police and the Community in Crime Prevention Efforts by the Directorate of General Criminal Investigation in Jambi Province - Anindito, Dhadhag; Koto, Zulkarnaen; Setiono, Joko (Greenation Publisher & Yayasan Global Resarch National, 2025)
This study discusses the synergy between the police and the community in crime prevention efforts, focusing on the role of the Directorate of General Criminal Investigation (Ditreskrimum) of the Jambi Regional Police. Crime prevention is not solely the responsibility of the police institution but requires the active involvement of the community as a strategic partner. This study uses a normative juridical approach to examine the legal framework governing such cooperation, including Law No. 2 of 2002 concerning the Indonesian National Police, Police Regulation No. 1 of 2021 on Community Policing, and Police Regulation No. 14 of 2018 in conjunction with Police Regulation No. 3 of 2024, which regulate the organization and core duties of Ditreskrimum at the regional police level. The study finds that Ditreskrimum has implemented various preventive strategies, such as dialogic patrols, the establishment of partnership forums, and legal education for the public. However, the implementation of this synergy still faces multiple challenges, including limited resources, low public legal awareness, and weak oversight of program implementation. Additionally, discrepancies between the regulatory framework and on-the-ground practices hinder the long-term effectiveness of this synergy. The study recommends strengthening personnel capacity, providing local policy support, and developing evaluation systems and administrative sanctions as solutions to establish a more equitable, participatory, and sustainable partnership in crime prevention.